Documentation of Ethnoveterinary Practices in the CKNP Region, Gilgit-Baltistan - Iftikhar Ali; Hidayat Hussain; Huma Batool; Akber Dad; Ghulam Raza; Abiodun Falodun; Raza Ullah; Viqar Uddin Ahmad (International Journal of Phytomedicine, 2017)
Majority of the livestock holders in different areas of Central Karakoram National Park (CKNP) region in Gilgit-Baltistan lack the modern veterinary healthcare facilities. The local community mostly depends upon the traditional floral therapeutic veterinary practices for the cure of various livestock diseases. The lack of the ethnoveterinary surveys in the CKNP region results in loss in the scientific documentation of the traditional information and practices about the livestock healthcare. The present study deals with the documentation of the livestock diseases and the ethnoveterinary herbal and non-herbal therapeutic practices by the livestock holders in CKNP region. The study was conducted from March 2012 to March 2013 in the valleys of CKNP region. The ethnoveterinary data was collected through the semi-structured questionnaires and the techniques of interviews and field visits. And the productive interaction provided an enabling background for the successful Rapid Rural Appraisal and Participatory Rural Appraisal research. Total 156 local community members were interviewed in Thallay, Khaplu, Hushe and Shigar valleys. The survey showed the prevalence of the most common diseases e.g. FMD, intestinal problems etc. Among the 51 medicinal plants, the Asteraceae family exhibited the highest number of genera with the therapeutic species. The parts of the plants that were most frequently used for the therapeutic purposes were the leaves (55%), seed (15%) etc. The present study contributed to the documentation of the medicinal plants used in the ethnoveterinary practices in valleys in CKNP region, Gilgit-Baltistan.